A dinâmica inovativa das empresas de pequeno porte no Brasil - Graziela Ferrero Zucoloto; Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper analyzes the innovative performance of Brazilian industrial companies according to their size. We obtained the data from the Innovation Survey 2011, published by the Brazilian Institute of Geography and Statistics (IBGE). We grouped the companies according to their size: micro and small (between 10 and 99 employees), medium (100-499 employees) and large (500 or more employees). The paper not only analyzed the innovation rates of such groups, but the degree of innovativeness, differences in innovative activities, the degree of cooperation, use of public incentives, among others. In addition, the work carries out a sectoral analysis of the companies, according to the established sizes. Among the main results, it concluded that despite the large firms present innovative rates higher than small ones, innovative efforts of these are proportionally higher, with emphasis on the acquisition of machine, which is associated with the modernization of the production process. Still, small businesses are the main responsible for the introduction of new products in the domestic and world market, accounting for about 3/4 full. Regarding the R&D efforts in low-tech sectors, the distance of SMEs to large firms is significant, while in the more technology-intensive industries, such as pharmaceutical, information technology and electronics, the smaller companies have technological effort higher than that of large companies.
Keywords: L53; O31; O38; 330; firms size; micro and small business; innovative activities; brazilian industry; innovation; public policy